Effect of Hormone Replacement Therapy (HRT) and low-dose combined oral pill on skin thickness, lipid profile and blood chemistry of menopausal women (Faculty of Medicine Universitas Indonesia, 2003)
This study to evaluate the effect of hormone replacement therapy ( HRT ) and low-dose combinated oral pill on skin thickness , lipid profile and blood chemistry on menopausal woman.This study was carried out in one year randomized prospective study. 36 women were divided into 18 women receiving HRT and the other 18 receiving low-dose oral pill. The result of this study showed an increase in skin thickness (collagen) in both groups. But Those received low dose oral pill showed more . The increase of the skin thickness can prevent osteoporosis. The administration of HRT or low-dose oral pill could cause allteration in blood lipip profile and blood chemistry. But The changes were still within in normal limit. The administration of low-dose oral pill can be considered in postmeno-pausal women. (Med J Indones 2003; 12: 224-8)